Alternating R‐CHOP and R‐cytarabine is a safe and effective regimen for transplant‐ineligible patients with a newly diagnosed mantle cell lymphoma. Issue 1 (30th October 2017) - Klener, Pavel; Fronkova, Eva; Belada, David; Forsterova, Kristina; Pytlik, Robert; Kalinova, Marketa; Simkovic, Martin; Salek, David; Mocikova, Heidi; Prochazka, Vit; Blahovcova, Petra; Janikova, Andrea; et al.
Abstract: Implementation of cytarabine into induction therapy became standard of care for younger patients with mantle cell lymphoma (MCL). On the basis of its beneficial impact, many centers incorporated cytarabine at lower doses also into first‐line treatments of elderly patients. We conducted a multicenter observational study that prospectively analyzed safety and efficacy of alternating 3 + 3 cycles of R‐CHOP and R‐cytarabine for newly diagnosed transplant‐ineligible MCL patients. A total of 73 patients were enrolled with median age 70 years. Most patients had intermediate (39.7%) and high‐risk (50.7%) disease according to MCL international prognostic index. Rituximab maintenance was initiated in 58 patients. Overall response rate reached 89% by positron emission tomography–computed tomography, including 75.3% complete remissions. Two patients (2.7%) did not complete the induction therapy because of toxicity. Three patients (4.1%) were considered nonresponders, which led to therapy change before completion of induction. Estimated progression‐free survival and overall survival were 51.3% and 68.6% at 4 years, respectively. Mantle cell lymphoma international prognostic index, bulky disease (≥ 5 cm), and achievement of positron emission tomography–negativity independently correlated with progression‐free survival. Grade 3 to 4 hematologic and nonhematologic toxicity was documented in 48% and 20.5% patients, respectively. Alternation of R‐CHOP and R‐cytarabine represents feasible and very effective regimen for elderly/comorbid MCL patients. This study was registered at GovTrial (clinicaltrials.gov ) NCT03054883.